Merajut Keberagaman : Diversitas Sosiokultural dalam Pendidikan Agama Islam di Indonesia - Navisah Al Ainiyah; Nihayatur Rofiqoh; Fina Qotrunnada Fuadiyah; Muhammad Adib Nuruzzaman; Muhammad Toha Sobirin (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
This article examines the important role of education in managing sociocultural diversity in Indonesia, which is a diverse country. Sociocultural diversity, which includes differences in ethnicity, religion, gender, and culture, is an integral part of Indonesian society. Islamic Religious Education (IRE) has great potential to promote tolerance, inclusivity, and social cohesion in this diverse context. Through literature review, this study analyzes how IRE can be effectively implemented to address diversity. The concepts of Jean Piaget and Lev Vygotsky's cognitive psychology theories are important foundations for understanding how students construct religious understanding in their socio-cultural context, with a focus on the interaction between individual cognitive development and the influence of the social environment in the internalization of multicultural values. A culturally responsive learning approach and the integration of multicultural values into the PAI curriculum are key. However, the article also identifies challenges such as a lack of teacher training and resistance to change. To that end, collaboration between schools, teachers, parents, and the community is necessary to create an inclusive and peaceful learning environment. Innovation in PAI teaching methods, such as contextual approaches, project-based learning, and the use of technology, is also important for the relevance and effectiveness of religious education in Indonesia.